The Intervening Effect of Customer Satisfaction at 212 Mart - Nafisatul Husniah; Muhamad Ahsan; Nurhayati Nurhayati (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2023)
Today, many sharia minimarkets are operating in Indonesia, including 212 Mart. This minimarket was inspired by Aksi Bela Islam 212. Despite emphasizing sharia values, customer loyalty is still the primary determinant of the success of a business. This study aimed to analyze and prove the variable influence of religiosity, brand equity, and service quality on customer loyalty with customer satisfaction as an intervening variable in the 212 Mart DKI Jakarta area. The quantitative method is used to prove the hypothesis proposed by the research sample of 136 respondents (response rate of 82%). The data were collected using the purposive sampling technique through a questionnaire given directly to the respondents. The collected data were analyzed using Partial Least Square through the SmartPLS 3.0 application. The results showed; that first, there was a direct influence on the variable of religiosity and service quality on customer loyalty and the variable of service quality on customer satisfaction. Second, the effect of religiosity, brand equity, and service quality on customer loyalty is not mediated by customer satisfaction as an intervening variable. The uniqueness of this result is that customer satisfaction does not judge the effect of other variables on customer loyalty at 212 Mart. In the future, it is essential to know whether the same applies to other sharia-based minimarkets.